(3GdWQjbI GdeMeOjIs - (3GdHQcdj, GdHQchj, GdQhej, eMj GdOjf, eMeO Hf HjQ Ydj Hf GScfOQ, J (B981 (3g`s ((3MSf Hf eQGOs)
(3ChdgG (B:s
(3GdMeO ddg GdPj LYdfG CeI hSWG aEf GdYbd hGdfbd eJhGabGf hGdcJGH hGdSfI eJWGHbGf Ydi Cf GdOfjG SQjYI GdRhGd hGdNQGH hQJHJg Ydi KdGKI CHhGHs
(3BNQgG (B:s
(3GdaUd GdKGdK aj CehQ eHJOYI HGWdI efgG hba GdChbGa SjeG GdfbhO dJdGhI GdbQBf GdYXje Ch dCf jUdj fhGad Ch dCf jSHM Ch dCf jUdj Ydi GdfHj hjYWj KhGHgG dQhM GdhGba Ch dQhM ef CQGOg Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6/61s
(3cTa GdXfhf (B2/1111s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs